2013
DOI: 10.5901/mjss.2013.v4n4p59
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Engineering Communicative Challenges amongst Undergraduates

Abstract: Much has been said in the Malaysian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Although the findings of different studies about the dissemination processes related to the policy are contradictory, the key issue observed in both Yusoff and Samah (2013) and Ali's (2013b) study was that whether it is through a top-down or bottom-up approach, the implementation of EMI policy is problematic. The factor that could lead to the success of implementing a policy depends on the willingness of an individual to do so.…”
Section: English As the Medium Of Instructionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the findings of different studies about the dissemination processes related to the policy are contradictory, the key issue observed in both Yusoff and Samah (2013) and Ali's (2013b) study was that whether it is through a top-down or bottom-up approach, the implementation of EMI policy is problematic. The factor that could lead to the success of implementing a policy depends on the willingness of an individual to do so.…”
Section: English As the Medium Of Instructionmentioning
confidence: 99%
“…These issues are engineering students' limited communicative abilities due to their limited proficiency in English (Che Musa, Lie, & Azman, 2012b;Yusoff & Samah, 2013), engineering educators' understandings of EMI, and the manner in which EMI policy was disseminated (Ali, 2013a;2013b). In a study to examine the learning of content in English in higher education it was found that the students had difficulties in understanding the content when lectures were conducted in English (Che Musa et al, 2012b).…”
Section: English As the Medium Of Instructionmentioning
confidence: 99%
See 3 more Smart Citations